Solace Island - Tilly, Meg (Jove, 2018)
"A contemporary novel with a strong suspense element from Oscar-nominated actress Meg Tilly set on a peaceful island village in the Pacific Northwest. Dumped on the eve of her wedding and looking for a quiet place to lick her emotional wounds, Maggie Harris joins her sister on Solace Island, where she hopes to recover from the stunning betrayal. At first, Maggie resists Eve's impassioned argument about relocating permanently so the sisters can open their own local bakery. What she definitely doesn't need on her road to recovery are Eve's efforts to fix her up with their mysterious and alluring neighbor, Luke Benson--even if he is incredibly handsome and desirable. Just as Maggie starts to get comfortable in her new surroundings, a car tries to run her down in the middle of the street. If it weren't for Luke's extremely quick reflexes, Maggie could have been killed, leading her to wonder just who exactly Luke Benson really is... Luke thought he'd left the violence of the high risk security world behind. But he can't stand by while Maggie's life is threatened. Luke will do anything to keep her safe--even moving Maggie and her sister into his house with its state-of-the-art security features. But with the secrets between them and an unknown threat stalking her heels, Luke will have to think fast to prove to Maggie that she can trust him with her life--and with her heart"--